FORMULASI DAN UJI AKTIVITAS SABUN CAIR KULIT NANAS DENGAN PENAMBAHAN JERUK PURUT - Angga Tritisari; Andi Maryam; Hamdi; Rona Safrina (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Pineapple (Ananas comosus (L.) Merr.) is a fruit that is widely available and popular among the public. Various products made from processed pineapple inevitably result in waste, particularly pineapple peels. The research was conducted in the Food Processing Laboratory and the Quality Analysis Laboratory of the Agribusiness Department, Sambas State Polytechnic. The research was carried out from May to October 2024. The experimental design used was a Factorial Completely Randomized Design (CRD) with two factors: the concentration of pineapple peel (Factor A) (levels: 100%, 75%, 50%, 25%) and the concentration of kaffir lime (Factor B) (5%, 10%, 15%, 20%), resulting in 4 treatment combinations. Liquid dishwashing soap made from pineapple peel with the addition of kaffir lime in formulations SP1 (100%; 5%), SP2 (75%; 10%), SP3 (50%; 15%), and SP4 (25%; 20%) showed good quality, with detergent pH ranging from 7.03 to 7.23; specific gravity from 1.079 to 1.083 g/ml, foam stability from 96.92% to 99.12%, and no free alkali content or bacterial contamination, meeting the SNI standards of < 25 colonies/g. The liquid dishwashing soap made from pineapple peel with the addition of kaffir lime also demonstrated stable foaming power.